The Cambridge companion to European novelists - Bell, Michael, 1941- (Cambridge ; New York : Cambridge University Press, 2012)
"A lively and comprehensive account of the whole tradition of European fiction for students and teachers of comparative literature, this volume covers twenty-five of the most significant and influential novelists in Europe from Cervantes to Kundera. Each essay examines an author's use of, and contributions to, the genre and also engages an important aspect of the form, such as its relation to romance or one of its sub-genres, such as the Bildungsroman. Larger theoretical questions are introduced through specific readings of exemplary novels. Taking a broad historical and geographic view, the essays keep in mind the role the novel itself has played in the development of European national identities and in cultural history over the last four centuries. While conveying essential introductory information for new readers, these authoritative essays reflect up-to-date scholarship and also review, and sometimes challenge, conventional accounts"--
Machine generated contents note: Introduction: the novel in Europe, 1600-1900 Michael Bell; 1. Miguel de Cervantes Edwin Williamson; 2. Daniel Defoe Cynthia Wall; 3. Samuel Richardson Thomas Keymer; 4. Henry Fielding Thomas Lockwood; 6. Jean-Jacques Rousseau Timothy O'Hagan; 7. Laurence Sterne Michael Bell; 8. Johann Wolfgang von Goethe Martin Swales; 9. Walter Scott Susan Manning; 10. Stendhal Ann Jefferson; 11. Mary Shelley David Punter; 12. Honore; de Balzac Michael Tilby; 13. Charles Dickens John Bowen; 14. George Eliot John Rignall; 15. Gustave Flaubert Timothy Unwin; 16. Fyodor Dostoevsky Sarah Young; 17. Leo Tolstoy Donna Tussing Orwin; 18. Emile Zola Brian Nelson; 19. Henry James Angus Wrenn; 20. Marcel Proust Marion Schmid; 21. Thomas Mann Ritchie Robertson; 22. James Joyce Christopher Butler; 23. Virginia Woolf Laura Marcus; 24. Samuel Beckett Leslie Hill; 25. Milan Kundera Rajendra A. Chitnis; Conclusion: the European novel after 1900 Michael Bell; Further reading; Index.
Includes bibliographical references (p. 444-447) and index.
Keywords: European fiction -- History and criticism; LITERARY CRITICISM / European / General